Blood-supplementing effect of low molecular weight peptides of E-Jiao on chemotherapy-induced myelosuppression: evaluation of pharmacological activity and identification of bioactive peptides released in vivo - Zhang, Jinju; Lin, Danlin; Wu, Yuting; Chen, Lixia; Ma, Zhiguo; Wu, Menghua; Liu, Xindan; Zhang, Ying; Cao, Hui (Frontiers in Pharmacology, 2024)
Equus asinus L. [Equidae; Asini Corri Colla] (donkey-hide gelatin, E-Jiao) is a traditional Chinese medicine renowned for its exceptional blood-supplementing effect. However, the specific components that contribute to its efficacy remain elusive. This study aimed to demonstrate that peptides are responsible for E-Jiao's blood-supplementing effect and to explore the specific peptides contributing to its efficacy. The low molecular weight peptides of E-Jiao (LMEJ) were obtained using an in vitro digestion method, and a total of 660 unique peptides were identified within it. Both E-Jiao and LMEJ significantly alleviated myelosuppression in mice but only LMEJ attenuated myelosuppression in zebrafish. Moreover, after the administration of E-Jiao to rats, 67 E-Jiaoderived peptides were detected in the bloodstream, 41 of which were identical to those identified in LMEJ. Out of these 41 peptides, five were synthesized. Subsequent verification of their effects revealed that two of them were able to alleviate myelosuppression in zebrafish. Network pharmacology and molecular docking studies suggested that E-Jiao may exert a bloodsupplementing effect by regulating signaling pathways such as JAK-STAT, IL-17 and others. These results indicated that peptides are at least partially responsible for E-Jiao's efficacy. This study provides a crucial foundation for further exploration of the bioactive components of E-Jiao.